Effectiveness of The Futsal Passing Exercise Model Based on Small-Sided Games for The Middle School Levels - Praniata, Agus Rizqi; Kridasuwarso, Bambang; Puspitorini, Wahyuningtyas (Department of Physical Education, Sport, Health and Recreation, 2019)
The study was conducted to find out the results of the effectiveness test of the futsal-based small-sided games training model at the high school level. This type of research used research and development with pre-test and post-test. The research subjects used were 30 futsal players at the high school level in the city of Bandung. The type of data collection method in this study uses quantitative and qualitative methods. The research resulted in the effectiveness of the calculation results using SPSS 16 with the mean pre-test = 6.3667 and the mean post-test = 8.4000, the difference in the results of the pre-test and post-test or mean difference = -2.03333, t -count = -15.503, df = = 29 and p-value = 0.00 <0.05. then there is a significant difference in value between the previous value and the value after being treated with a model of futsal passing training based on small-sided games. These results show that the model of futsal passing training has effective small-sided games used for futsal passing exercises.